Can the gamma-ray source 3EG J2033+4118 be produced by the stellar system Cygnus OB2 No. 5? - Benaglia, Paula (2001)
We discuss the possibility that the stellar system Cyg OB2 No. 5 can be a gamma-ray source in the light of recent EGRET and radio data. This system is formed by an O7 Ia + Ofpe/WN9 contact binary. A third star, probably a B0 V star also associated with the system, is located at ∼1700 AU from the primary. We estimate the expected gamma-ray luminosity from the colliding winds region, the terminal shock of the wind, and the unstable zone at the base of the wind, and conclude that, under very reasonable assumptions, Cyg OB2 No. 5 can generate about a half of the gamma-ray flux detected from the positionally coincident source 3EG J2033+4118. We suggest, then, that other O stars belonging to the association, also placed within the 95% probability EGRET location contour, could contribute to the observed gamma-ray flux.